Avoiding unconscious injection of vial-derived rubber particles during intra-articular drug administration - Andreas Hecker; Agostino Di Maro; Emanuel F. Liechti; Frank M. Klenke (Osteoarthritis and Cartilage Open, 2021)
Objective: Vial coring describes the occurrence of small rubber particles, which are formed by needles when perforating vial stoppers. These particles may be aspirated along with the drug. Unconscious injection of rubber particles may increase the risks associated with intra-articular injections. This study aimed to analyze the frequency of this phenomenon and possibilities to avoid its occurrence. Method: 800 vials of 2 ​mL, filled with sodium chloride, were divided into 4 groups (n ​= ​200 each). Aspiration through the rubber stopper was performed with a 18-Gauge needle and the fluid was ejected onto a 10 ​μm filter paper through a 18-Gauge needle (group one) and a 23-Gauge needle (group two). In group three a 23-Gauge needle was used for aspiration and ejection. In group four, aspiration was performed using 18-Gauge needles with implemented 5 ​μm filters. Subsequently, a microscopic analysis of the filter papers was performed. Results: In none of the 800 specimen, a rubber particle was detected by naked eye. Microscopically, 20 (10%) rubber particles were detected in group one, 21 (11%) in group two and 65 (33%) in group three. In group four, no particles were visualized. Conclusion: This study shows the occurrence of rubber particles in 10–33% of the cases, when standard needles are used for the aspiration of drugs. We therefore recommend using industrially prefilled syringes, filter needles or removing the rubber stopper before withdrawing drugs from vials for intra-articular injections.